EPIDEMIOLOGICAL ASSESSMENT OF TRAUMATIC SPINAL FRACTURES - MáRCIO PAPALEO DE SOUZA; VICTOR CéSAR GAVA VICENTI; VICTOR HUGO JACQUES VIEIRA; JULIANA ROBERTA NEMETZ DE OLIVEIRA (Coluna/Columna)
ABSTRACT Objective: To conduct an epidemiological assessment of traumatic spinal fractures that occurred between March 2023 and March 2024 in a referenced tertiary hospital. Methods: A retrospective cross-sectional observational epidemiological study aimed at evaluating the profile of patients with spinal fractures treated at a tertiary hospital specializing in spinal fractures in Santa Catarina, between March 2023 and March 2024. Results: The majority of patients were male (58.9%), with a mean age of 47.94 ± 17.44 years. The most frequent trauma mechanism was falls from height (37.7%), followed by traffic accidents (37.0%). The L1 vertebra was the most affected (26.7%). The AO classification showed a predominance of type A1 fractures (30.8%). Most patients (87.7%) did not present neurological deficits. Conservative treatment was indicated in 67% of cases, while 33% required surgical intervention. Conclusion: Traumatic spinal fractures are more common in men at working age, associated with falls from height and traffic accidents, and in elderly women, associated with ground-level falls. The high prevalence of fractures in these groups reinforces the need for preventive policies focused on traffic safety and fall prevention programs for the elderly. Level of Evidence II; Prognostic Study.